2022
DOI: 10.3389/fphys.2022.815766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extended Underwater Sections on the Physiological and Biomechanical Parameters of Competitive Swimmers

Abstract: Despite changes in the underwater sections of swimming races affecting overall performance, there is no information about the effects of the apnea-induced changes on the physiological state of competitive swimmers. The aim of the present research was to examine the effect of changes in the underwater race sections on the physiological [blood lactate concentration, heart rate, and rating of perceived exertion (RPE)] and biomechanical (underwater time, distance, and velocity) parameters of competitive swimmers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The present analysis was conducted without knowledge about specific race strategies applied by the swimmers. As individual race strategies may influence turn phases, i.e., by increasing the underwater phase to reduce wave drag [47][48][49], previous studies have proposed using individualized distance, rather than fixed-distance measurements, to investigate inter-individual turn strategies [35]. However, fixed-distance measurements are still commonly used for regular assessment of the training process using simple tools, such as stopwatches, and for obtaining comparative data for race analyses during competitions [11].…”
Section: Discussionmentioning
confidence: 99%
“…The present analysis was conducted without knowledge about specific race strategies applied by the swimmers. As individual race strategies may influence turn phases, i.e., by increasing the underwater phase to reduce wave drag [47][48][49], previous studies have proposed using individualized distance, rather than fixed-distance measurements, to investigate inter-individual turn strategies [35]. However, fixed-distance measurements are still commonly used for regular assessment of the training process using simple tools, such as stopwatches, and for obtaining comparative data for race analyses during competitions [11].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, higher-ranked swimmers achieved faster underwater velocities and underwater distances were related to swimming performance (Pla et al, 2021). However, lack of oxygen due to restricted breathing results in apnea-induced discomfort (Veiga et al, 2022). In order to not interfere with transition and clean swimming phases, the length of the underwater phase should match an individual's optimum rather than maximum (Veiga et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, lack of oxygen due to restricted breathing results in apnea-induced discomfort (Veiga et al, 2022). In order to not interfere with transition and clean swimming phases, the length of the underwater phase should match an individual's optimum rather than maximum (Veiga et al, 2022). Specific breathing maneuvers and apnea training regimes may help to achieve longer underwater phases (Woorons et al, 2016;Robertson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study conducted by ( Clifford et al, 2016 ) demonstrated an improvement in physical performance measured by countermovement jumping when supplementing with BJ. The improved blood flow during physical exercise could also contribute to the decrease in the subjective perception of effort ( Jodra et al, 2019 ) and could be effective in situations where oxygen availability is less ( Kelly et al, 2014 ; Flueck et al, 2016 ), as occurs in swimming, especially during the underwater sections ( Veiga et al, 2022 ). However, very little research has explored the benefits of BJ supplementation in competitive swimmers, especially in relation to the repeated efforts that characterize swimming competitions.…”
Section: Introductionmentioning
confidence: 99%